Autism spectrum disorder : understanding and management through countering violent extremism strategies : a thesis presented in fulfilment if the requirements for the degree of Master of Health Science in Psychology at Massey University, New Zealand - Power, Amy (Massey University, 2022)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterised by persistent social and cognitive deficits presenting in adolescent developmental phase. There are three categories of impairment that can occur; language skills, social behaviour, and cognitive functioning, which can lead to atypical interpretations of surrounding environments. Although expression of ASD characteristics varies across individual circumstances, common behaviours identified across the cohort are suggested to influence perceptions of social law and consequences, and susceptibility to radicalisation to violent extremism. Violent extremism (VE) is a global problem that has led countries such as New Zealand, Australia, United Kingdom, and Canada, to develop Counter-Violent Extremism strategies to minimize the impact of VE. The current research explores how these strategies attend to the specific needs and impairments of autistic individuals. Chapter one explores autism and violent extremism and how they may link. Examination is made of the current understandings around autism and how this neurodevelopmental disorder may be linked with expressions of violent extremism. Chapter two provides an account of the chosen methodology of Document Analysis, the analysis processes undertaken and the ethical considerations. Chapter three provides the results of the study, structured by way of themes and sub-themes found across the dataset. The final chapter consists of a discussion regarding each theme and how it corroborates with previous research. This chapter will also explore the strengths and limitations that occurred when implementing this study and outlines any recommendations of future research direction.
Keywords: 520599 Social and personality psychology not elsewhere classified